Prevalence Study of Pulmonary Tuberculosis in Umbulharjo Sub-District Yogaykarta 2014-2016 - Desi Nurfita; Fatma Nurasyiah; Atikah Rahayu (International Journal of Healthcare Research, 2018)
Background : Pulmonary tuberculosis is infectious disease coused by Mycobacterium tuberculosis. Most of Mycobacterium tuberculosis attacks lungs, but it can also attack other body organs (Depkes RI, 2007). Tuberculosis remains one of the deadliest diseases in the world. The World Health Organization (WHO) estimates that each year more than 8 million new cases of tuberculosis occur and approximately 3 million persons die from the disease. The result of Riskesdas in 2007, prevalence of pulmonary tuberculosis increases with age and highest prevalence is over 65 years. The prevalence of pulmonary tuberculosis in men is 20 % higher than woman. Prevalence of pulmonary tuberculosis is three times higher in low education compared to higher education (Riskesdas, 2007).Method : This type of study was quantitative descriptive research. Respondents were tuberculosis program holders at Health Primary Care of Umbulharjo 1 and Health Primary Care of Umbulharjo 2. This reseach used tuberculosis register in Health Primary Care of Umbulharjo 1 and Health Primary Care of Umbulharjo 2. Data analysis was performed by descriptive. Data analysis used frequency distribution analysis.Result : Suspected tuberculosis has increased from 2014 to 2016 in Umbulharjo District. Percentage of tuberculosis patients among the suspects in 2014 was 26.1%. Percentage of TB patients among the suspects in 2015 was 22.3%. Percentage of TB patients among the suspects in 2016 was 25.1%. the result of study foundÂ  pulmonary tuberculosis primer, pulmonary tuberculosis secondary, extrapulmonary tuberculosis, and tuberculosis in children. Treatment success rates reached 89% in 2014, 92% in 2015, and 78% in 2016.Conclusion : Cases of pulmonary tuberculosis fluctuate every year. Increased in 2016, which was 46 cases, compared to the year 2015 as many as 26 cases and in 2014 as many as 28 cases.